1, 2‐Bis(diphenylphosphino)ethane (dppe)/NBS: An Unprecedented Combination for Deoxygenation of Sulfoxides Under Mild Conditions. Issue 35 (13th September 2022) - Joshi, Asha; Iqbal, Zafar; De, Saroj Ranjan
Abstract: A novel, efficient and metal‐free strategy for the deoxygenation of sulfoxides to sulfides has been disclosed under mild conditions using dppe/NBS reagent system. Among several developed methods using phosphine based ligands, very few are convenient as most of them are confined to harsh reaction conditions, inseparable side products, moderate yields, and the use of costly and toxic reagents. The developed dppe/NBS promoted deoxygenation strategy tolerates a wide range of functional groups to afford good yields of desired sulfides. Abstract : We have disclosed a novel, efficient and metal‐free strategy for the deoxygenation of sulfoxides to sulfides under mild conditions using dppe/NBS reagent system. The reaction tolerates a wide range of functional groups to afford good yields of desired sulfides.